(untitled) (Global Journal of Management and Business Research, 2020)
This research aims to investigate the impact of job characteristics on job performance in the Greater Amman Municipality. The population of this research consisted of all employees working in the Greater Amman Municipality. A random sample was selected to collect data from the research population, which consisted of (400) questionnaires distributed to employees, while the returned questionnaires and valid to statistical analysis were (375) questionnaires, with the responding rate (94%). Structural Equation Modelling (SEM) was used as a statistical analysis method to achieve the research objectives and testing hypothesis.